Performa Panel Surya 2 X 50 WP pada Mesin Panen Padi Mini Dua Lajur - Susanto, Herdi; Darsan, Herri; Mukhlizar, Mukhlizar; Fitriadi, Nuzuli (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
Rice harvesting machines that can be operated in swampy, peatland, narrow and can be operated and maintained by farmers, can be considered for design, some previous research has been carried out, including a two-lane mini rice harvester with a performance of 20.33 hours per hectare and has been in manufacturing and in performance tests. Experimental studies on engine performance were carried out in this research. This research uses 2x50 watt peak polycrystalline solar panels connected to a 12 volt 45 AH battery, the battery will drive a 50 watt electric motor. Current and voltage measurements are carried out on the solar panel and battery when in condition, first the solar panel is connected to the battery and not connected to the electric motor, the second solar panel is connected to the battery and connected to the electric motor, the three solar panels are not connected to the battery and the battery is connected to electric motor. The results of the first condition study indicate that the electric current will be more stable using a new battery, when compared to using a battery in the previous study. The second condition was that the performance of the two-lane mini rice harvester increased by 50% when compared to the performance of an electric motor using a battery that was not connected to a solar panel. The third condition shows the performance of the electric motor has increased by up to 300% when compared with the results of previous studies, it is estimated that the electric motor will continue to rotate for up to 8-10 hours